Кейтеринг у MICE-індустрії: тренди розвитку, міжнародний досвід і перспективи digital-трансформації - Якименко-Терещенко, Наталія Василівна; Чайка, Тетяна Юріївна; Бєлікова, Олена Станіславівна (My University, 2021)
У статті розглянуті тенденції та перспективи розвитку індустрії гостинності, а також деякі найперспективніші інноваційні digital-рішення у сфері надання послуг кейтерингу для MICE-заходів: цифрові ваучери, гастро-меппінг, набори для онлайн-кейтерингу. Приділено увагу комплексному підходу до формування інноваційних бізнес-моделей на основі digital-трансформації. Криза, що була викликана пандемією COVID-19, поставила на межу банкрутства значну частину економічних агентів. У такій ситуації на економічне процвітання можуть розраховувати ті суб'єкти підприємницької діяльності, які оперативно відмовляться від застарілих бізнес-моделей. Тільки комплексне та системне використання інноваційних рішень, формування нових інноваційних бізнес-моделей здатне забезпечити підприємство конкурентною перевагою та запобігти негативному сценарію розвитку подій. У статті вдосконалено підхід та розроблено практичні рекомендації щодо впровадження конкретних інноваційних цифрових технологій у базові компоненти бізнес-процесів з метою формування нової бізнес-моделі на основі комплексного використання digital-рішень.

The purpose of this paper is: to study the trends and prospects for the hospitality industry; to clarify the possibilities of using the most promising innovative digital solutions in catering services for MICE-Events (digital vouchers, gastro-mapping, online catering kits, etc.); to improve a comprehensive approach to building innovative business models based on the digital transformation of catering firms specializing in meeting the needs of the MICE-Industry. The COVID-19 pandemic crisis has brought a large proportion of economic agents to the brink of bankruptcy. In such a situation, only those business entities that promptly abandon outdated business models can count on economic prosperity. Only comprehensive and systematic use of innovative solutions, the creation of new innovative business models can provide the company with a competitive advantage and prevent a negative scenario. Research methods. When studying the trends of the hospitality industry in Ukraine, statistical methods of time series analysis were used. Theoretical and applied analysis of digital technologies, promising from the point of view of application in catering support of MICE-Events, was carried out using logical-analytical and system-structural research methods. The scientific novelty of the study lies in clarifying the prospects and features of the introduction of digital technologies in the field of catering for the MICE-Industry. The study of the mechanism of digital transformation of business models has been further developed. The practical significance of the results lies in the possibility of their use in tactical and strategic planning of the activities of firms specializing in the provision of catering services for MICE-Events. Prospects for further research may be related to the concept of sustainable development in the implementation of theoretical and applied analysis of digital transformation of business processes of firms specializing in the provision of catering services for MICE-Events.
Catering for MICE-Industry: development trends, international experience, and digital-transformation prospects
Keywords: кейтеринг; онлайн-кейтеринг; спеціальний туризм; діловий туризм; MICE-індустрія; діджиталізація; digital-трансформація; інновації; бізнес модель; цифрові ваучери; гастро-меппінг; набори для онлайн-кейтерингу; catering; online catering; special interest tourism; business tourism; MICE-Industry; digitalization; digital-transformation; innovation; business model; digital vouchers; gastro mapping; online catering kits